EPISODIC CONCEPTUALISATION–A POSSIBLE SOURCE OF ALTERNATIVE CONCEPTION ABOUT ’KINETIC ENERGY’ AND ’WORK’ - Arora, O.P.; Mohapatra, J.K.; Parida, B. K. (SCHOOL SCIENCE, 2010)
In recent times, ‘Episodic Conceptualisation’ has been identified as one of the origins of pupils’ alternative conceptions. It is hypothesized that the episodic format of the form, content, and mode of presentation of the concepts ‘Kinetic Energy’ and ‘Work’ in the textbook as well as in the classroom by the teacher is likely to generate in the minds of the pupils two isolated, mutually independent cognitive structures. It is conjectured that any task, which demands conceptual and/or mathematical correlation between these two concepts, is likely to bring to the fore pupils’ alternative conceptions that are reflections of the above ‘Episodic Conceptualisation’. The results of the present study do indicate that there are enough evidences to put faith on our hypothesis and conjecture in the framework of these two concept labels.